Eucalyptus in Extension Forestry Programmes of the Agricultural State of Punjab - Singh, Jagjit (Indian Forester, 1975)
In this paper, the locality factors about the state of Punjab, area under forests, vegetation and the availability of forest products, etc, have,been recorded. Punjab, being an agricultural State, is highly deficient in timber and firewood. Against the demand of 700,000 m3 of timber, only 44,000 m3 are produced and, against a demand of 2,600,000 m3 of firewood, only 28,000 m3 of firewood are available from recorded sources. To make up the deficiency of firewood, cow-dung manure, maize stalks, cotton sticks and other agricultural residues are used in rural areas to provide energy. In order to make up the deficiency of wood, Eucalyptus plantations have been raised during last ten years covering about 11,570.8 hectares of block forests, strips, river banks, etc., in the State. On evaluation, 4500 hectares have been found to be successful. In addition to this, farmers have raised Eucalyptus trees on the boundaries of agricultural fields, irrigation channels, ’phirnies’, wells, tube-wells, compounds of buildings, farm paths, etc., on a large scale. Eucalyptus is very much liked by the farmers as a farm tree. The growth statistics, economics and marketing of these plantations have been discussed. There is a vast scope for extending planting on farms and village link roads and in State forests. It has been advocated that other agricultural States of India should also take to the planting of Eucalyptus or other fast growing species suited to local conditions to meet the deficiency of wood in rural, urban and industrial sectors.